Endo-esophageal mechanical injuries - Vega, Dardo E (Cirugía del Uruguay, 1975)
The esophagus may be injured from its lumen, either during endoscopy or by an ingested foreign body. In both situa tions, the types of lesions are similar: minlmal injury , tearing of the mucosa, and complete perforation. They present common diagnostic and therapeutic problems, which are discussed in the present work. In 2,500 esophagoscoples períormed by the author, onIy 6 complete perforations occurred (one In every 415 cases) -3 oí them dicd -and only one se...cre blecding.